Protest leadership in the age of social media. Issue 7 (2nd July 2016) - Poell, Thomas; Abdulla, Rasha; Rieder, Bernhard; Woltering, Robbert; Zack, Liesbeth
ABSTRACT: This article challenges the idea that social media protest mobilization and communication are primarily propelled by the self-motivated sharing of ideas, plans, images, and resources. It shows that leadership plays a vital role in steering popular contention on key social platforms. This argument is developed through a detailed case study on the interaction between the administrators and users of the Kullena Khaled Said Facebook page, the most popular online platform during the Egyptian revolution of early 2011. The analysis specifically focuses on the period from 1 January until 15 February 2011. It draws from 1629 admin posts and 1, 465, 696 user comments, extracted via a customized version of Netvizz. For each day during this period, the three most engaged with posts, as well as the 10 most engaged with comments, have been translated and coded, making it possible to systematically examine how the administrators tried to shape the communication on the page, and how users responded to these efforts. This analysis is pursued from a sociotechnical perspective. It traces how the exchanges on the page are simultaneously shaped by the admins' marketing strategies and the technological architecture of the Facebook page. On the basis of this exploration, we argue that the page administrators should be understood as 'connective leaders'. Rather than directing protest activity through formal organizations and collective identity frames, as social movement leaders have traditionally done, connective leaders invite and steer user participation by employing sophisticated marketing strategies to connect users in online communication streams and networks.